Predicting adult metabolic syndrome from childhood body mass index: follow-up of the New Delhi birth cohort. Issue 10 (17th November 2008) - Sachdev, H P S; Osmond, C; Fall, C H D; Lakshmy, R; Ramji, S; Dey Biswas, S K; Prabhakaran, D; Tandon, N; Reddy, K S; Barker, D J P; Bhargava, S K
Abstract : Objectives: To assess whether serial measurements of childhood body mass index (BMI) give clinically useful predictions of the risk of developing adult metabolic syndrome and impaired glucose tolerance or type 2 diabetes. Design/setting: Follow-up of a community-based birth cohort in Delhi, India. Participants: 1492 men and women aged 26–32 years whose BMI was recorded 6-monthly throughout childhood. Main outcome measures: The predictive value of childhood BMI for adult metabolic syndrome and impaired glucose tolerance (IGT) and diabetes mellitus. Results: 25% of subjects had metabolic syndrome and 15% had IGT/diabetes mellitus. Both outcomes were associated with greater childhood BMI gain (metabolic syndrome: OR 1.63 (95% CI 1.44 to 1.85); IGT/diabetes mellitus: 1.39 (1.20 to 1.60) per unit increase in within-cohort BMI SD score between 5 and 14 years). The best predictions of adult disease were obtained using a combined test comprising (i) any increase in BMI SD score between 5 and 14 years and (ii) a BMI SD score >0 at 14 years (metabolic syndrome: sensitivity 45%, specificity 78%; IGT/diabetes mellitus: 37%, 73%). Likelihood ratios were low (metabolic syndrome: 1.4–2.0; IGT/diabetes mellitus: 1.2–1.4). A single high BMI measurement at 14 years (overweight or obese, according to International Obesity Task Force criteria) was highly specific but insensitive (metabolic syndrome: sensitivity 7%, specificity 97%; IGT/diabetes mellitus: 8%, 97%). Charts for plotting BMI SD scores through childhood were produced. Conclusions: Serial measurements of childhood BMI give useful predictions of adult risk and could guide advice to children and parents on preventing later disease.